Removal of Phenol Contaminants from Aqueous Solution Using Pickering Emulsion Liquid Membrane Stabilized by Magnetic Nano-Fe3O4 - Rasool, Tamara L.; Mohammed, Ahmed A.; Ravankhah, Vida (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
In the current study, the effect of the nonionic surfactant (span 80) on the emulsification of a mixture of kerosene as a petroleum-based organic solvent and span80 as a green diluent in the ratio 1:1 was investigated. NaOH was used as the internal phase, and the stability of the emulsion was tested. The potential for extracting phenol from aqueous solutions without the use of a carrier agent has been explored using Pickering emulsion liquid membrane. Additionally, the impacts of experimental parameters include homogenizer speed, mixing speed, emulsification time, Fe3O4-Span 80 ratios, NaOH concentration, and internal to membrane volume ratio (I/O) on extraction effectiveness and emulsion stability. The findings demonstrated that after 9 minutes of contact time and a minimum breaking percent of 0.745% under ideal circumstances, more than 96% of phenol could be recovered. In addition thermodynamic analysis reveals that the extraction process was an endothermic and spontaneous in nature and the overall mass transfer coefficient was 1.115 m/s. Membrane materials and nanoparticles were recycled four time in the extraction of phenol with approximately the same efficiency and no significant breakage percent..